2016
DOI: 10.1038/leu.2016.49
|View full text |Cite
|
Sign up to set email alerts
|

Re-activation of mitochondrial apoptosis inhibits T-cell lymphoma survival and treatment resistance

Abstract: T lymphocyte non-Hodgkin's lymphoma (T-NHL) represents an aggressive and largely therapy-resistant subtype of lymphoid malignancies. As deregulated apoptosis is a frequent hallmark of lymphomagenesis, we analyzed gene expression profiles and protein levels of primary human T-NHL samples for various apoptotic regulators. We identified the apoptotic regulator MCL-1 as the only pro-survival BCL-2 family member to be highly expressed throughout all human T-NHL subtypes. Functional validation of pro-survival protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…In line with previous reports in alternative cancer cohorts 12 , 22 , genomic gains of MCL-1 occurred at higher frequency than any other BCL-2 family member and did not cause compensatory deregulation of other BCL-2 protein family members, as detected in the TCGA and TRACERx datasets. This has already been shown in hepatocellular carcinoma 28 , B cell-non-Hodgkin’s lymphoma 29 and T cell lymphoma 23 , 30 , 31 . However, dependencies on other pro-survival BCL-2 family members may exist depending on the type of cancer and treatment used, as recently reported data on breast cancer showed a positive correlation between not only MCL-1 but also BCL-2A1 expression and an inverse association with BCL-2 expression 26 .…”
Section: Discussionmentioning
confidence: 54%
“…In line with previous reports in alternative cancer cohorts 12 , 22 , genomic gains of MCL-1 occurred at higher frequency than any other BCL-2 family member and did not cause compensatory deregulation of other BCL-2 protein family members, as detected in the TCGA and TRACERx datasets. This has already been shown in hepatocellular carcinoma 28 , B cell-non-Hodgkin’s lymphoma 29 and T cell lymphoma 23 , 30 , 31 . However, dependencies on other pro-survival BCL-2 family members may exist depending on the type of cancer and treatment used, as recently reported data on breast cancer showed a positive correlation between not only MCL-1 but also BCL-2A1 expression and an inverse association with BCL-2 expression 26 .…”
Section: Discussionmentioning
confidence: 54%
“…Analysis of large cancer genome datasets revealed that the genomic region containing MCL1 is amplified in $10% of cancers (Beroukhim et al, 2010). Of note, inducible gene deletion in pre-clinical murine models of cancer showed that MCL-1 is essential for the sustained expansion of acute myeloid leukemia (AML) (Glaser et al, 2012), c-MYC-or BCR-ABL-driven pre-B or B cell lymphomas (Kelly et al, 2014;Koss et al, 2013), T cell lymphomas driven by loss of p53 or other oncogenic lesions Spinner et al, 2016), and multiple myeloma (MM) Morales et al, 2011). The development of S63845 provided the first opportunity to test an MCL-1-selective BH3-mimetic drug in pre-clinical cancer models (Kotschy et al, 2016).…”
Section: Figure 2 New Bh3-mimetic Drugs: Expected Efficacy and Predimentioning
confidence: 99%
“…Within pro-survival BCL-2 members, myeloid cell leukemia-1 (MCL-1) was identified as an important anti-apoptotic protein in several lymphoma subtypes. [1][2][3] Interestingly, despite BCL-2 and MCL-1 being the only anti-apoptotic BCL-2 family members that are located on chromosomal fragile sites (Table 1), MCL-1 is rarely a target for chromosomal translocation. A possible reason for this difference may lie in a recombination hotspot intersecting with the BCL-2, but not the MCL-1, gene.…”
Section: Genetic Aberrations In Lymphomamentioning
confidence: 99%